Analysing the Conversion of a Cultural Heritage to a Multi-functional Complex in the Context of Sustainability: Example of Fiume Veneto - Ozer, Yasemen Say; Ozer, Nevzat Oguz (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2011)
Fiume Veneto, was established on the banks of the river Fiume near the city of Pordenone in northern Italy. What makes this settlement distinctive is the huge yarn factory which was founded sometime between 1880 and 1885. The textile factory has offices and a clean electrical power plant (hydroelectric), both located on an island of about 100,000 square metres. There is also a building located outside the factory, in which there had been a grain mill serving the locals since the XIIIth century up until its closure in 1999. Following its closure, Isola del Fiume Company purchased the former textile factory together with the island in order to construct a multi-functional complex. In 2003, The City Council Planning Committee and the Italian Chamber of Architects decided to organize an international 'architectural design competition' under the supervision and policy of the International Union of Architects. The aim was to decide the best strategy to reuse the property as a whole and in consideration with the economic viability, an important criterion for the company. After setting up a jury, a programme was announced which included housing, facilities, the renovation of the mill and hydroelectric plant, the establishment/protection of green spaces, sports facilities, a civic centre and town hall, a museum and an auditorium as well as the necessary infrastructure related to the new development. The main theme of this article is an architectural competition in the context of sustainability and the ways in which structural comfort is achieved in the architectural solutions provided.
Keywords: FiumeVeneto; cultural heritage; architectural design; Architecture